2019
DOI: 10.1002/ejp.1415
|View full text |Cite
|
Sign up to set email alerts
|

Pain and posttraumatic stress disorder in refugees who survived torture: The role of pain catastrophizing and trauma‐related beliefs

Abstract: Background Traumatized refugees with comorbid pain report more severe posttraumatic stress disorder (PTSD), respond less well to PTSD‐focused treatments and exhibit greater disability. A mutually maintaining relationship may exist between pain and PTSD, that may be partly accounted for by depression, but no prior studies have tested this assumption in traumatized refugees. Method Self‐report measures of pain, PTSD, depression, disability, pain catastrophizing (PC) and trauma‐related beliefs (TRBs) were adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…45 This is important in a population where such catastrophic beliefs are believed to contribute to the maintenance of comorbid pain and PTSD. 46,47 It was not clear what drove the overly biomedical approach to pain diagnosis and treatment; a question perhaps better explored through the clinician's lens. It is possible that barriers to effective communication, as discussed above, could lead to superficial exploration of torture-survivors' pain and suffering.…”
Section: Discussionmentioning
confidence: 99%
“…45 This is important in a population where such catastrophic beliefs are believed to contribute to the maintenance of comorbid pain and PTSD. 46,47 It was not clear what drove the overly biomedical approach to pain diagnosis and treatment; a question perhaps better explored through the clinician's lens. It is possible that barriers to effective communication, as discussed above, could lead to superficial exploration of torture-survivors' pain and suffering.…”
Section: Discussionmentioning
confidence: 99%
“…The Danish Institute Against Torture (DIGNITY) is a self-governing institution with a governmentfunded clinic that provides inter-disciplinary, multimodal treatment targeting PTSD, depression, health problems and social integration in refugees who are survivors of torture or other organized forms of violence. Previous studies carried out with patients from this clinic have reported on the relationship between PTSD, chronic pain, and quality of life (Carlsson, Mortensen, & Kastrup, 2006;Harlacher et al, 2016;Olsen, Montgomery, Bojholm, & Foldspang, 2007), and that pain severity accounted for 66% of the variance in PTSD severity prior to treatment (Nordin & Perrin, 2019). In a preliminary fashion, the primary purpose of this study is to investigate the extent to which pre-treatment pain (severity and interference) predicts outcomes (PTSD, depression, and anxiety) in a multimodal treatment for refugees.…”
Section: Introductionmentioning
confidence: 98%
“…Many survivors have issues with chronic pain, even years after they have experienced torture (Amris et al, 2019). The location of pain is at times correlated with the type and location of torture, such as having foot pain after sustaining falanga torture (Prip et al, 2016), head pain after traumatic brain injury, shoulder pain following suspension, and pelvic and back pain following sexual torture (Amris et al, 2019;Baird et al, 2017;Kaur et al, 2020;Nordin & Perrin, 2019;Olsen et al, 2007;Tsur et al, 2020;Wang et al, 2016;Williams & Baird, 2016). .…”
Section: Chronic Pain In Survivors Of Torturementioning
confidence: 99%